Efficient cellular entry of (r-x-r)-type carbamate-plasmid DNA complexes and its implication for noninvasive topical DNA delivery to skin - Vij, Manika; Natarajan, Poornemaa; Yadav, Amit K.; Patil, Kiran M.; Pandey, Tanuja; Gupta, Nidhi; Santhiya, Deenan; Kumar, Vaijayanti A.; Fernandes, Moneesha; Ganguli, Munia (Molecular Pharmaceutics, 2016)
Arginine-rich cell penetrating peptides are powerful tools for in vitro as well as in vivo delivery of a wide plethora of biomolecules. However, presence of consecutive arginine residues leads to enhanced amenability for proteolytic degradation as well as steric hindrances for membrane interactions which compromise its bioavailability. In order to overcome these limitations we previously reported a safe and stable octaarginine based oligomer, i.e., (r-x-r)4-carbamate, where the backbone amide linkages were replaced by carbamate linkages and 6-aminohexanoic acid based spacer moieties were incorporated for better flexibility, hydrophobicity, optimal spacing of guanidinium groups, and protection against proteolytic cleavage; resulting in improved transfection efficiency over its amide counterpart. In the present work we have investigated the mechanism behind this enhanced transfection efficiency and, based on our observations, demonstrate how the synergistic effect of rationalized oligomer designing, complex characteristics, and cell type contributes to overall effective intracellular delivery. Our results indicate that the (r-x-r)4-carbamate plasmid DNA complexes primarily utilize lipid raft dependent pathway of cellular entry more than other pathways, and this possibly facilitates their increased entry in the lipid raft rich milieu of skin cells. We also emphasize the utility of oligomer (r-x-r)4-carbamate as an efficient carrier for topical delivery of nucleic acids in skin tissue. This carrier can be utilized for safe, efficient, and noninvasive delivery of therapeutically relevant macromolecular hydrophilic cargo like nucleic acids to skin.
Keywords: Cell penetrating peptides; endocytosis; nucleic acid delivery; skin penetration; transfection